Problems in aspect oriented design (AOD) - Ošmianskij, Vladislav; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2004)
The paper aims to evaluate the state of the art of AOD. It discusses main approaches to aspect modelling with UML, investigates the impact of aspects on 00 design methods and identifies open issues of AOD.